2019
DOI: 10.3390/coatings9030187
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Coated Micro Glass Spheres to Increase the Infrared Reflectance

Abstract: The reflective properties of micro glass spheres (MGS) such as Solid Micro Glass Spheres (SMGS, “glass beads”) and Micro Hollow Glass Spheres (MHGS, “glass bubbles”) are utilized in various applications, for example, as retro-reflector for traffic road stripe paints or facade paints. The reflection behavior of the spheres can be further adapted by coating the surfaces of the spheres, e.g., by titanium dioxide or a metallic coating. Such coated spheres can be employed as, e.g., mid infrared (MIR)-reflective add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The XRD pattern of the MF-organo-clay-pumice-hollow-glass-sphere hybrid composite (MFCPHHC) in Figure 5 shows the overlapping MF, pumice and amorphous silica peaks and the smectite peak almost disappeared. Thus, as expected, the pumice plates and hollow glass spheres encapsulated by spherical polymer clay nanocomposites exhibited an ordered and relatively discrete arrangement (see Figures 2f and 3f) [79,87,93].…”
Section: Characterization Of Mineralogical Structures Of Raw Montmori...supporting
confidence: 78%
“…The XRD pattern of the MF-organo-clay-pumice-hollow-glass-sphere hybrid composite (MFCPHHC) in Figure 5 shows the overlapping MF, pumice and amorphous silica peaks and the smectite peak almost disappeared. Thus, as expected, the pumice plates and hollow glass spheres encapsulated by spherical polymer clay nanocomposites exhibited an ordered and relatively discrete arrangement (see Figures 2f and 3f) [79,87,93].…”
Section: Characterization Of Mineralogical Structures Of Raw Montmori...supporting
confidence: 78%
“…Special attention has been paid to the coating of microspheres with various materials for properties improvement: to increase porosity and decrease density, preserve compressive strength, in some cases catalytic properties, modification of thermal conductivity or dielectric properties, achieve higher thermal resistance than materials which exhibit similar density. Therefore, coatings prepared from different materials such as copper [46], molybdenum oxide [47], and aluminum [48] were developed.…”
Section: Introductionmentioning
confidence: 99%
“…Schwinger et al [25] discuss a novel, non-vacuum, liquid phase method of depositing thin films of aluminium on spherical glass substrates, comparing the results to those obtained by a more conventional physical vapour deposition (PVD) process for reference. It is reported that reflectance of solid micro glass spheres can be increased by around 30%, a comparable result to that achieved using PVD.…”
mentioning
confidence: 99%